Influence ARCS (Attention, Relevance, Confidence, Satisfaction) Motivation and Interest in Learning Outcomes Students in the Anthroposphere Material of Geography Subjects Class XI MIPA at SMA Negeri 1 Sindue Tombusabora - Kiki; Zeffitni; Rifai (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
As a teacher is not only on his ability in develop knowledge knowledge , will but more on his ability For carry out interesting and meaningful learning .​ The nature of the teacher is impressive dominate moment giving material lessons , without interspersed actions that can be make participant educate more relax and happy follow the learning process . With the emergence of boredom in self participant educate will result in lack of Power absorb participant educate to the material taught so that will affect the results Study participant educate . Research This use approach quantitative and apply method experiment , namely For researching Influence ARCS Motivation ( Attention, Relevance, Confidence, Satisfaction ) and Interest in Learning Outcomes Student in the Anthroposphere Material of Geography Subject Class XI MIPA at SMA Negeri 1 Sindue Tombusabora . In addition researchers also use technique correlation For know direction and data collection will be done in study This that is with use method questionnaire , which is in the form of statements and questions written given​ direct to respondents . Based on from results posttest that has been analyzed obtained average value of results Study student MIPA Class 1 as class experiment of 79.00 and Class MIPA 2 as class control with average value of results Study that is 64.88 can proven that there is difference results Study student Mathematics Class 1 at State Senior High School 1 Sindue Tombusabora which means hypothesis work (Ha) in study This accepted , while the null hypothesis (Ho) is rejected . That figure show existence influence ARCS Motivation ( Attention, Relevance, Confidence, Satisfaction ) and Interest in Learning Outcomes Student in the Anthroposphere Material of Geography Subject Class XI MIPA at SMA Negeri 1 Sindue Tomb Raider .